The effect of coffee and black tea consumption on sleep bruxism intensity based on polysomnographic examination - Weronika Frosztega; Mieszko Wieckiewicz; Dorian Nowacki; Rafal Poreba; Gabriella Lachowicz; Grzegorz Mazur; Helena Martynowicz (Heliyon, 2023)
Background: Sleep bruxism (SB) is a common behavior that can result in various clinical consequences on human health. Risk factors for SB include among others emotional stress, anxiety, tobacco smoking, and excessive alcohol consumption. Coffee and black tea are among the most commonly consumed beverages worldwide. This study explores the influence of coffee and black tea consumption on bruxism intensity, as observed in polysomnographic examination. Methods: Polysomnographic examination with simultaneous camera recording was conducted in 106 adult subjects. The results were evaluated according to guidelines set out by the American Academy of Sleep Medicine (AASM). The study group was divided according to habitual stimulant usage, as declared by the participants in a self-reported questionnaire. Four groups were identified: coffee drinkers versus non-drinkers and black tea drinkers versus non-drinkers. Results: The bruxism episode index (BEI) was increased in coffee-drinkers as opposed to non-drinkers (4.59 ± 3.44 vs. 2.87 ± 1.50, p = 0.011). Sleep fragmentation, measured according to the arousal index, was comparable in coffee drinkers and non-drinkers. Electrolyte and lipid levels were similar in coffee drinkers and non-drinkers. Habitual black tea intake did not affect sleep architecture or bruxism intensity. Conclusions: The study showed that habitual coffee consumption is a risk factor for the increased intensity of sleep bruxism. Neither coffee nor tea consumption is related to sleep fragmentation in habitual drinkers. Coffee and tea intake does not affect electrolyte and lipid concentrations. Caution should therefore be recommended in drinking coffee in people with sleep bruxism.